Interplay health communication in new media in healthy living attitudes in Indonesia - K. Y. S. Putri; Engkus Kuswarno; Heri Fathurahman; Praventyasar Mutiara (Universitas Negeri Yogyakarta, 2023)
Health communication has become important after two years of the world experiencing Covid 19. The quality of healthy life in the community is important. New media make good information about maintaining health. However, because of the long period of being in normal healthy conditions, many new media accounts provide incorrect health information. The research question is how effective is health communication in the content of its messages in the new media about health in the post-pandemic period against the healthy living attitudes of its followers? The purpose of the study was to find out health communication in the content of its messages in new media about health in the post-pandemic period towards the healthy living attitudes of its followers. The concepts of health communication, healthy living attitudes, and previous research support this research. Health communication has the dimensions of interpersonal communication and mass communication. A healthy life attitude has cognitive, affective, and conative dimensions. This research method uses quantitative by distributing questionnaires to respondents. The validity and reliability of the measuring instrument is valid and reliable so that it can be continued to the next statistical analysis. The results of descriptive research are of good value to all dimensions, both health communication variables and attitude variables. The analysis of the next two variables is that both have strong effectiveness. The interplay of both variables is considered strong according to the applicable standards according to some literature. This means that the effect of health communication in new media is effective in influencing the life attitudes of the Indonesian people. So the alternative hypothesis of this study is accepted, and the null hypothesis is rejected. The results of this study are related to previous studies. So that it can be utilized by subsequent research and health communication academics. Research suggestions can be developed from other theoretical perspectives and use other methods to enrich the development of health communication studies.